Atherosclerosis: a complex interplay of inflammatory processes. (April 2009) - Harangi, Mariann; Szodoray, Peter; Paragh, Gyöörgy
Recently, atherosclerosis has been recognized as a chronic inflammatory disease, characterized by the activation of cells with phagocytotic and antigen-presenting capabilities, accumulation of oxidatively modified lipoproteins, increased in situ turnover of immune-competent cells and tissue damage, as well as hypertrophic degeneration of the arterial intima. Both cellular and humoral components of the immune system have been implicated in these atherosclerotic processes. The aim of the present review is to summarize the potential harmful immune-inflammatory steps in the development of atherosclerosis and to depict the therapeutic regimens presently in use, as well as to envision future drug developments that will hopefully be beneficial in the battle against this disease.